The right to prior consultation and the cultural survival guarantee of indigenous peoples in Peru, regarding the granting of mining concessions - Másquez Salvador, Álvaro (2019)
This article aims to demonstrate, based in national and international law, the State obligation to consult mining concessions with indigenous peoples in Peru, in a context of neo-extractivism. Similarly, intends to evidence that the arbitrary expedition of concessions in indigenous territories may harm or extinct their cultural manifestations, due to the relations among prior consultation and their political, territorial and cultural rights.This means a threat for their cultural survival. For this, cases of Quechua and Aimara peoples will be analyzed, as they graphic a pattern of indigenous rights’ violations.